CEH Certified Ethical Hacker practice exams - Walker, Matthew (McGraw-Hill Education, 2014)
Fully revised for the new CEH v.8 exam objectives from the EC-Council, this practical guide provides 500+ simulated CEH exam questions with in-depth answer explanations.